Membangun Identitas Digital Workshop Pembuatan Website Dengan Wordpress (Pesantren At-Taubah Karawang) - Sukmawati, Cici Emilia; Juwita, Ayu Ratna; Novalia, Elfina; Nurmayanti, Trisya; Tejayanda, Rigger Damaiarta; Faisal, Muhamad Agus (Indonesian Scientific Journal, 2024)
Workshop